INCORPORATING CASE STUDIES IN CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) FOR ENGLISH LANGUAGE DEVELOPMENT OF TRAINEES IN THE MALAYSIAN ARMED FORCES - Amalanathan, Enock (Tesis, 2021)
The aim of this research is to identify the effectiveness of case studies in content and language integrated learning (CLIL) for English language development of trainees in the Malaysian Armed Forces (MAF).